Effects of Physical Display Size on GUI Designers' Perception and Implementation of Usability Guidelines - Kaptan, Selvihan Nazli; Göktürk, Mehmet (Springer-Verlag Berlin, 2011)
Recent advances in technology led to common use of large screen in daily use. Applications of large displays are categorized in three groups; private, semi-public and public applications. Private and semi-public displays allow visualization and manipulation of large amounts of data at once. The increase in display size leads to an increase in data amount, which in result causes users to adopt a complex way of use. These changes arise the need for research in usability, interaction and user performance aspects of large displays. This study evaluates the effect of physical display size and resolution on GUI designers' perception and implementation of usability guidelines. Results suggest that subjects perform better on large displays for visual search and comparison tasks such as checking alignment, visual format similarities, etc. Reading related evaluations, on the other hand, are not supported by the larger displays.
1st International Conference on Design, User Experience, and Usability (DUXU)/14th International Conference on Human-Computer Interaction (HCI) -- JUL 09-14, 2011 -- Orlando, FL
Keywords: large displays; physical screen size; user performance; usability